Under the Bleachers
XII, 144 p.
Keywords: “The field of education can be a rewarding, but ever challenging career. This book is an essential read for new teachers and veteran teachers alike. The insightful stories that Dr. Joseph Jones has masterfully chosen as part of the book will inspire a new sense of resolve and hope for those who are feeling the weight of seemingly impossible demands placed on teachers. These compelling excerpts will assist the reader through the maze of uncertainty that many new teachers face.” --Wendi West Veteran Teacher Elementary, Virginia Under the Bleachers: Teachers’ Reflections of What They Didn’t Learn in College is a unique text because the chapters offer insight into the daily chaos of teaching. The chapters are written by practicing educators and provide advice to both future educators and current teachers. It is important to mention, the text is not an avenue to criticize teacher education programs; rather, the book opens a dialogic space in which all educators can begin discussing and reflecting on the realities of the schooling process.